Correction: A fluorescent biosensor for cardiac biomarker myoglobin detection based on carbon dots and deoxyribonuclease I-aided target recycling signal amplification. Issue 20 (27th April 2022) - Chen, Jishun; Ran, Fengying; Chen, Qinhua; Luo, Dan; Ma, Weidong; Han, Tuo; Wang, Ceming; Wang, Congxia
Abstract : Correction for 'A fluorescent biosensor for cardiac biomarker myoglobin detection based on carbon dots and deoxyribonuclease I-aided target recycling signal amplification' by Jishun Chen et al., RSC Adv., 2019, 9, 4463–4468, ; https://doi.org/10.1039/C8RA09459D .